Who owns the city? Neoliberal urbanism and land purchases in Gurgaon, India - Bhagia, Meher; Bose, Mallika (Urban Studies, 2024)
Increasing purchases of valuable real estate for storing capital have contributed to the soaring prices of modest housing in many global cities and in several South Asian cities such as Mumbai, Delhi and Bangalore. Saskia Sassen has drawn attention to the phenomenon of underutilisation of purchased properties existing alongside the acute demand for housing by low- and moderate-income households in the same cities. Despite the gravity of this issue, empirical analyses of urban land transactions remain rare, especially because such purchases often tend to be piecemeal and obscure, involving a multitude of smaller land deals and a variety of actors. This paper examines corporate purchases of urban land in Gurgaon, a city adjacent to New Delhi that has embraced neoliberal economic policies. By creating a land database for the upcoming sectors in the city, the study makes sharply visible: (1) the radical changes in property ownership patterns from agricultural land to luxury gated communities, (2) the growing corporate investments, extreme concentration of land ownership and deeply unequal distribution of urban land and (3) the use of various illicit practices by market-leading companies in land banking.
Keywords: Corporate Land Ownership; Illicit; Neoliberal Urbanism; Urban Land Grab; India